Women and Christianity in fifth-century Ireland Women and Christianity in fifth-century Ireland: an analysis of Patrick’s Confessio - Mattana, Clarissa (Romanitas - Revista de Estudos Grecolatinos, 2026)
This article focuses on the forms of religious life adopted by women after conversion to Christianity in regions considered borderlands with the Roman West. One of our main witnesses to this phenomenon is a text attributed to Patrick, known as Confessio, written in Ireland in the 5th century. Considering the historical context of profound religious, cultural, and social transformations of Late Antiquity, the following objectives were outlined: to analyze the evidence of possible female experiences within the scope of Patrick's evangelizing mission in Ireland; to investigate how the author positioned himself on the issue of women in newly converted Christian communities; and to discuss how he would have mobilized these issues while constructing the defense against his detractors, which permeates the text of the Confessio.
Keywords: Ireland; Women; Conversion; Religious life; Chastity